123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191192193194195196197198 |
- from sympy.core.logic import (fuzzy_not, Logic, And, Or, Not, fuzzy_and,
- fuzzy_or, _fuzzy_group, _torf, fuzzy_nand, fuzzy_xor)
- from sympy.testing.pytest import raises
- from itertools import product
- T = True
- F = False
- U = None
- def test_torf():
- v = [T, F, U]
- for i in product(*[v]*3):
- assert _torf(i) is (True if all(j for j in i) else
- (False if all(j is False for j in i) else None))
- def test_fuzzy_group():
- v = [T, F, U]
- for i in product(*[v]*3):
- assert _fuzzy_group(i) is (None if None in i else
- (True if all(j for j in i) else False))
- assert _fuzzy_group(i, quick_exit=True) is \
- (None if (i.count(False) > 1) else
- (None if None in i else (True if all(j for j in i) else False)))
- it = (True if (i == 0) else None for i in range(2))
- assert _torf(it) is None
- it = (True if (i == 1) else None for i in range(2))
- assert _torf(it) is None
- def test_fuzzy_not():
- assert fuzzy_not(T) == F
- assert fuzzy_not(F) == T
- assert fuzzy_not(U) == U
- def test_fuzzy_and():
- assert fuzzy_and([T, T]) == T
- assert fuzzy_and([T, F]) == F
- assert fuzzy_and([T, U]) == U
- assert fuzzy_and([F, F]) == F
- assert fuzzy_and([F, U]) == F
- assert fuzzy_and([U, U]) == U
- assert [fuzzy_and([w]) for w in [U, T, F]] == [U, T, F]
- assert fuzzy_and([T, F, U]) == F
- assert fuzzy_and([]) == T
- raises(TypeError, lambda: fuzzy_and())
- def test_fuzzy_or():
- assert fuzzy_or([T, T]) == T
- assert fuzzy_or([T, F]) == T
- assert fuzzy_or([T, U]) == T
- assert fuzzy_or([F, F]) == F
- assert fuzzy_or([F, U]) == U
- assert fuzzy_or([U, U]) == U
- assert [fuzzy_or([w]) for w in [U, T, F]] == [U, T, F]
- assert fuzzy_or([T, F, U]) == T
- assert fuzzy_or([]) == F
- raises(TypeError, lambda: fuzzy_or())
- def test_logic_cmp():
- l1 = And('a', Not('b'))
- l2 = And('a', Not('b'))
- assert hash(l1) == hash(l2)
- assert (l1 == l2) == T
- assert (l1 != l2) == F
- assert And('a', 'b', 'c') == And('b', 'a', 'c')
- assert And('a', 'b', 'c') == And('c', 'b', 'a')
- assert And('a', 'b', 'c') == And('c', 'a', 'b')
- assert Not('a') < Not('b')
- assert (Not('b') < Not('a')) is False
- assert (Not('a') < 2) is False
- def test_logic_onearg():
- assert And() is True
- assert Or() is False
- assert And(T) == T
- assert And(F) == F
- assert Or(T) == T
- assert Or(F) == F
- assert And('a') == 'a'
- assert Or('a') == 'a'
- def test_logic_xnotx():
- assert And('a', Not('a')) == F
- assert Or('a', Not('a')) == T
- def test_logic_eval_TF():
- assert And(F, F) == F
- assert And(F, T) == F
- assert And(T, F) == F
- assert And(T, T) == T
- assert Or(F, F) == F
- assert Or(F, T) == T
- assert Or(T, F) == T
- assert Or(T, T) == T
- assert And('a', T) == 'a'
- assert And('a', F) == F
- assert Or('a', T) == T
- assert Or('a', F) == 'a'
- def test_logic_combine_args():
- assert And('a', 'b', 'a') == And('a', 'b')
- assert Or('a', 'b', 'a') == Or('a', 'b')
- assert And(And('a', 'b'), And('c', 'd')) == And('a', 'b', 'c', 'd')
- assert Or(Or('a', 'b'), Or('c', 'd')) == Or('a', 'b', 'c', 'd')
- assert Or('t', And('n', 'p', 'r'), And('n', 'r'), And('n', 'p', 'r'), 't',
- And('n', 'r')) == Or('t', And('n', 'p', 'r'), And('n', 'r'))
- def test_logic_expand():
- t = And(Or('a', 'b'), 'c')
- assert t.expand() == Or(And('a', 'c'), And('b', 'c'))
- t = And(Or('a', Not('b')), 'b')
- assert t.expand() == And('a', 'b')
- t = And(Or('a', 'b'), Or('c', 'd'))
- assert t.expand() == \
- Or(And('a', 'c'), And('a', 'd'), And('b', 'c'), And('b', 'd'))
- def test_logic_fromstring():
- S = Logic.fromstring
- assert S('a') == 'a'
- assert S('!a') == Not('a')
- assert S('a & b') == And('a', 'b')
- assert S('a | b') == Or('a', 'b')
- assert S('a | b & c') == And(Or('a', 'b'), 'c')
- assert S('a & b | c') == Or(And('a', 'b'), 'c')
- assert S('a & b & c') == And('a', 'b', 'c')
- assert S('a | b | c') == Or('a', 'b', 'c')
- raises(ValueError, lambda: S('| a'))
- raises(ValueError, lambda: S('& a'))
- raises(ValueError, lambda: S('a | | b'))
- raises(ValueError, lambda: S('a | & b'))
- raises(ValueError, lambda: S('a & & b'))
- raises(ValueError, lambda: S('a |'))
- raises(ValueError, lambda: S('a|b'))
- raises(ValueError, lambda: S('!'))
- raises(ValueError, lambda: S('! a'))
- raises(ValueError, lambda: S('!(a + 1)'))
- raises(ValueError, lambda: S(''))
- def test_logic_not():
- assert Not('a') != '!a'
- assert Not('!a') != 'a'
- assert Not(True) == False
- assert Not(False) == True
- # NOTE: we may want to change default Not behaviour and put this
- # functionality into some method.
- assert Not(And('a', 'b')) == Or(Not('a'), Not('b'))
- assert Not(Or('a', 'b')) == And(Not('a'), Not('b'))
- raises(ValueError, lambda: Not(1))
- def test_formatting():
- S = Logic.fromstring
- raises(ValueError, lambda: S('a&b'))
- raises(ValueError, lambda: S('a|b'))
- raises(ValueError, lambda: S('! a'))
- def test_fuzzy_xor():
- assert fuzzy_xor((None,)) is None
- assert fuzzy_xor((None, True)) is None
- assert fuzzy_xor((None, False)) is None
- assert fuzzy_xor((True, False)) is True
- assert fuzzy_xor((True, True)) is False
- assert fuzzy_xor((True, True, False)) is False
- assert fuzzy_xor((True, True, False, True)) is True
- def test_fuzzy_nand():
- for args in [(1, 0), (1, 1), (0, 0)]:
- assert fuzzy_nand(args) == fuzzy_not(fuzzy_and(args))
|